Global trends in stem education research (2000–2018): A systematic journal-based study - M, Ramadhevi; Prakash, S. Raja (Edelweiss Applied Science and Technology, 2025)
Researchers published in 36 publications to conduct a thorough analysis of the state of STEM education research from 2000 to 2018, according to Lin, et al. [1]. Unlike previous literature assessments that concentrated on a single discipline or journal, this review synthesizes trends in authorship geography, methodological approaches, thematic focus, and disciplinary representation. According to the study based on English [2] there has been a notable increase in STEM education research since 2010, as evidenced by the expansion of the STEM label’s usage, the rise in empirical work—especially quantitative work—and the preponderance of American writers. Policy, curriculum, and K–12 education were the main areas of inquiry, and seven significant thematic groups were found based on National Research Council [3]. While highlighting the dynamic and growing nature of STEM education research, these findings also point to limitations in theme diversity and global representation. These findings’ ramifications are examined in light of policy formation, educational equity, and the international exchange of knowledge.